Математическая модель гидроупругих колебаний составных оболочек, частично заполненных жидкостью - Кононенко, И.Ю.; Стрельникова, Е.А. (Видавничий дім "Академперіодика" НАН України, 2008)
A mathematical model of hydroelastic vibrations for partially filled compound shells of revolution is developed. The shell equilibrium equation and the Neumann problem are considered simultaneously to determine the fluid pressure upon the shell. The 2-dimensional Neumann problem is reduced to a 1-dimensional hypersingular integral equation. A method of discrete singularities is proposed for the numerical investigation of the derived integral equation.